The Impact of New Media on Policy Affecting Agriculture - Lauri M. Baker; Tracy Irani (Journal of Applied Communications, 2014)
New media have changed the way people communicate and transfer information, but their effects on agenda-setting and the transfer of salience of objects and attributes have not been explored empirically. This study utilized a quantitative content analysis to determine how the blogosphere affects the agricultural policy agenda by analyzing a specific piece of policy that has the potential to effect agriculture. Results indicate a significant predictive relationship of the blogosphere agenda, media agenda, interest group agenda, and public agenda to the policy agenda. This adds new information on agenda-setting in an online environment by concluding agenda-setting occurs in new media environments similarly to traditional media environments. Future studies should consider the influence of the blogosphere on the political agenda.
Keywords: Agricultural policy; agenda-setting; new media; blogosphere